2014
DOI: 10.1111/neup.12118
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous adenocarcinoma arising from supratentorial intramedullary neuroenteric cyst with broncho‐pulmonary differentiation

Abstract: Neuroenteric cysts are benign intradural endoderm cysts lined by gastrointestinal (GI) or tracheobronchial epithelial cells. Their malignant transformation is extremely rare and only six cases have been reported. In these cases, tissue lineage of the cystic endoderm cells giving rise to carcinoma was not clearly identified either as respiratory or as GI type. Herein, we report a case of mucinous adenocarcinoma arising from the neuroenteric cyst with broncho-pulmonary differentiation in the right cerebral hemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…Our literature search identified three cases of neurenteric cysts that underwent malignant transformation. [12][13][14] Combined with cases of intracranial neurenteric cysts with malignant features, eight cases of malignant neurenteric cysts have been reported in the literature (Table 1). Notably, all of these eight cases were observed in intracranial neurenteric cysts, and malignant transformation of a spinal neurenteric cyst has never been reported, although they occur much more frequently in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature search identified three cases of neurenteric cysts that underwent malignant transformation. [12][13][14] Combined with cases of intracranial neurenteric cysts with malignant features, eight cases of malignant neurenteric cysts have been reported in the literature (Table 1). Notably, all of these eight cases were observed in intracranial neurenteric cysts, and malignant transformation of a spinal neurenteric cyst has never been reported, although they occur much more frequently in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…1) Other than the cases of originally malignant neurenteric cysts, [7][8][9][10][11] the malignant transformation of benign neurenteric cysts is extremely rare. [12][13][14] In this report, we describe a case of a neurenteric cyst in the posterior fossa that eventually showed malignant transformation and intracranial metastasis and review of the relevant literature.…”
mentioning
confidence: 99%
“…Other reports have indicated that NCs are ~3 times more common in the spine compared with the brain (4); therefore, the lack of studies reporting an intraspinal NC with a malignant transformation is notable. In addition, in 3/9 studies, the NC was located in the supratentorial region (9,11,15), and 2 of those cases reported intramedullary lesions located in the cerebral hemisphere (9,11). Intracranial NCs that developed within the posterior fossa accounted for 70-90% of all intracranial NC cases (1).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, very few reports have described this unusual phenomenon (9)(10)(11)(12)(13)(14)(15)(16). Therefore, the demographic characteristics, treatment and prognosis of this type of NC is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In exceptional cases, multiple NCs in both the supratentorial and the infratentorial compartments have been documented [2,11,13,17,18]. There are 3 cases showed NCs in the supratentorial region [19][20][21], and 2 of these cases reported intramedullary lesions located in the cerebral hemisphere [19,20]. Intracranial NCs in the posterior fossa make up 70-90% of all intracranial NCs cases [9].…”
Section: Epidemiological Data Of Ncsmentioning
confidence: 99%